Clostridium difficile Hfq can replace Escherichia coli Hfq for most of its function - Caillet, Joel (Cold Spring Harbor Laboratory Press, 2014)
A gene for the Hfq protein is present in the majority of sequenced bacterial genomes. Its characteristic hexameric ring-like core structure is formed by the highly conserved N-terminal regions. In contrast, the C-terminal forms an extension, which varies in length, lacks homology, and is predicted to be unstructured. In Gram-negative bacteria, Hfq facilitates the pairing of sRNAs with their mRNA target and thus affects gene expression, either positively or negatively, and modulates sRNA degradation. In Gram-positive bacteria, its role is still poorly characterized. Numerous sRNAs have been detected in many Gram-positive bacteria, but it is not yet known whether these sRNAs act in association with Hfq. Compared with all other Hfqs, the C. difficile Hfq exhibits an unusual C-terminal sequence with 75% asparagine and glutamine residues, while the N-terminal core part is more conserved. To gain insight into the functionality of the C. difficile Hfq (Cd-Hfq) protein in processes regulated by sRNAs, we have tested the ability of Cd-Hfq to fulfill the functions of the E. coli Hfq (Ec-Hfq) by examining various functions associated with Hfq in both positive and negative controls of gene expression. We found that Cd-Hfq substitutes for most but not all of the tested functions of the Ec-Hfq protein. We also investigated the role of the C-terminal part of the Hfq proteins. We found that the C-terminal part of both Ec-Hfq and Cd-Hfq is not essential but contributes to some functions of both the E. coli and C. difficile chaperons.